Rare earth slurry for white dye with radiation cooling function and preparation method thereof
By using high -entropy rare earth materials, improve the refractive index and cover power of radiation refrigeration coatings, solve the problem of insufficient existing coating reflectivity and launch rate, achieve efficient radiation refrigeration effects, and reduce the cost of material preparation.
Patent Information
- Application Number
- CN202410042706.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-11
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-01-11
AI Technical Summary
The reflectivity and emissivity of existing radiation refrigeration coatings are insufficient, and the resin components will absorb infrared and ultraviolet rays, resulting in a degradation of coating performance, and the resin is prone to self-curing during storage. At the same time, the preparation of traditional high-entropy ceramic materials is expensive and cannot be mass-produced.
The high -entropy rare earth material is used to increase the disorder of the amorphous network structure by combining a variety of different content of rare earth elements, thereby increasing the refractive index and covering power of the coating. This method is directly separated from the rare soil of rare earth, and the preliminary separation of the precipitation method of sodium sulfate or sodium carbonate reinforcement salt is preliminarily separated, reducing the cost of preparation of materials.
It achieves high window emissivity and high reflectivity, reducing coating costs, and the material is green and environmentally friendly. It is suitable for fabrics, building exterior walls, roofs and oil storage tank surfaces, effectively reducing the surface temperature of objects.
Smart Images

Figure CN118006158B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, in particular to a rare earth slurry for white dyes with a radiation cooling function and a preparation method thereof. Background Art
[0002] With the increasing demand for energy-saving building materials in the whole society, radiation cooling paint is a new paint product in recent years among many energy-saving building materials. This coating product has both high sunlight reflection effect and high "atmospheric window" emission effect. High sunlight reflection performance can reduce the incident sunlight energy, while high "atmospheric window" emission performance can emit heat into outer space in the form of 8-13 micron thermal radiation, achieving heat dissipation and cooling effect. Applying radiation cooling paint to the wall can effectively reduce the incident external energy in the building, thereby achieving energy saving and consumption reduction.
[0003] The core material of radiant cooling coating is the functional filler in the coating. In the prior art, two types of fillers are usually used to achieve the radiant cooling function. The first type of material is the sunlight reflective filler. Among this type of filler, titanium dioxide is the most commonly used sunlight reflective filler with the best comprehensive performance, but it absorbs ultraviolet rays and causes the overall reflectivity to be low. The second type of material is the emissive filler. Common emissive fillers are silica microspheres and glass microspheres. This type of material has good emissive performance in the 9.2-micron far-infrared band. However, the emissive material will reduce the solid content of the reflective filler in the coating, thereby further reducing the reflectivity of the coating.
[0004] Traditional radiant cooling coatings all contain resin components, such as the radiant cooling coatings disclosed in patents such as CN202211068033.0, CN201910607455.2, and CN201911055405.4. These resin components can enhance the strength of the coating. However, the resin absorbs infrared rays in sunlight and reduces the solar reflectivity of the coating, resulting in low solar reflectivity of traditional radiant cooling coatings, and failure problems such as self-curing of the resin during long-term storage.
[0005] In addition, in view of the high heat absorption of traditional outdoor textile coatings under sunlight, the development of fabric coatings with cooling effects has become increasingly important. The fabric itself needs to have a certain degree of hiding power, which depends on the refractive index of the filler. The higher the refractive index of the filler, the higher the hiding power. Therefore, the less filler is needed, which will reduce costs and make the fabric lighter. High entropy soil refers to rare earths containing a variety of different rare earth elements. By adding high entropy soils with different contents of rare earth elements, the disorder in the amorphous network structure can be increased, thereby further improving the refractive index and hiding power of the coating. Traditional high entropy ceramics are made by combining different rare earth oxide materials in a certain proportion, but the preparation method of this high entropy soil material is expensive and cannot be mass-produced.
[0006] In summary, there is an urgent need for a method for preparing high-entropy soil materials with simple process and low cost, as well as a radiative cooling slurry for fabrics that does not add resin components and has high window emissivity and high reflectivity. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art, specifically a rare earth slurry for white dye with radiation cooling function and a preparation method thereof, so as to at least achieve the effect that the rare earth slurry has high window emissivity, high reflectivity and.
[0008] The objective of the present invention is achieved through the following technical solutions:
[0009] A rare earth slurry for white dye with radiation cooling function:
[0010] Calculated by weight, the raw materials include 20-35 parts of aluminum oxide, 25-36 parts of niobium oxide, 13-20 parts of cerium group rare earth, and 16-35 parts of lead oxide.
[0011] The cerium family rare earth is obtained by separating the raw rare earth by sodium sulfate double salt precipitation method or sodium carbonate double salt precipitation method. The raw rare earth comes from Shenghe Rare Earth, wherein the lanthanum content is 25-30%, the cerium content is 31-35%, the praseodymium content is 3-3.4%, the neodymium content is 2-2.5%, the promethium content is 10-13%, the samarium content is 15-18% and the europium content is 22-25%.
[0012] It is worth noting that in the present invention, high entropy rare earth materials are used to increase the refractive index. High entropy rare earth refers to the addition of a variety of rare earth elements with different contents to increase the disorder in the amorphous network structure, thereby further improving the refractive index and hiding power. The realization of traditional high entropy ceramics is to use different rare earth oxide materials for matching. The high entropy materials prepared by this method are expensive. In this patent, the realization of high entropy rare earths is to directly use the crude raw materials of cerium rare earth produced by Shenghe Rare Earth as raw materials, and use the natural matching of various rare earth elements in the crude rare earth to achieve high entropy. Here, the so-called cerium rare earth is to use sodium sulfate double salt precipitation method or sodium carbonate double salt precipitation method in the rare earth separation process to preliminarily separate cerium rare earth elements from yttrium rare earth elements. The cerium rare earth obtained contains seven rare earth elements: lanthanum, cerium, praseodymium, neodymium, promethium, samarium and europium. The present invention directly uses the crude rare earth separation as a raw material to prepare amorphous high entropy rare earth materials, which has extremely low cost.
[0013] The method for preparing the slurry comprises the following steps:
[0014] S1: mixing the aluminum oxide, niobium oxide, rare earth oxide and lead oxide and crushing them;
[0015] S2: sintering the crushed powder at high temperature, and then quenching the sintered molten liquid in cold water to obtain a coarse product powder;
[0016] S3: adding the crude product powder to a solvent for grinding to obtain A1 slurry with a particle size of 15-25 μm, A2 slurry with a particle size of 5-10 μm, and A3 slurry with a particle size of 0.3-0.7 μm;
[0017] S4: Grind the crude product powder with water, then perform atomization drying, and perform a second sintering at high temperature. The obtained powder is dispersed in a solvent to obtain A4 slurry;
[0018] S5: Mix the A1 slurry, A2 slurry, A3 slurry and A4 slurry to obtain.
[0019] It is worth noting that the essence of the filler reflecting infrared rays is Mie scattering with the incident light. Generally speaking, large-particle fillers have a better reflection effect on infrared rays with longer wavelengths, and small-size filler particles have a better reflection effect on incident light with shorter wavelengths. In the prior art, the fillers used are often subjected to a unified ball milling or sand milling process. In the slurry obtained in this way, the filler has a uniform particle size, which has a good reflection effect on incident light of a certain wavelength, but poor reflection performance for the full sunlight spectrum. In the present application, through process control, the powder material is first processed into an intermediate raw material with a certain particle size, and then the powders of each particle size distribution are mixed according to a certain content ratio, and finally a filler product with multiple particle size distributions is obtained, which can produce excellent reflection effects on sunlight of all wavelengths.
[0020] Furthermore, in step S2, the particle size of the crushed powder is 30-40 mesh.
[0021] Further, in step S2, the temperature of the first sintering is 1360-1400°C;
[0022] And / or, the first sintering time is 4-4.5h.
[0023] Furthermore, in step S4, the particle size of the coarse product powder after grinding is 1-5 μm.
[0024] Further, in step S4, the temperature of the second sintering is 1230-1250°C;
[0025] And / or, the second sintering time is 30-50 min.
[0026] Furthermore, the weight ratio of the A1 slurry, A2 slurry, A3 slurry and A4 slurry is 1:0.8-1.3:0.4-0.6:0.1-0.2.
[0027] It is worth noting that the filler particle size can not only affect the overall reflective properties of the filler, but also the emissive properties of the filler. By adding a type of filler with a specific particle size and special morphology to the radiative cooling coating, the emissivity can be further improved by utilizing its photon enhancement effect on infrared rays in the atmospheric window band.
[0028] Further, in steps S4 and S5, the solvent includes water or butyl acetate;
[0029] And / or, the solid content of the A1 slurry, A2 slurry, A3 slurry and A4 slurry is 30-40%.
[0030] The beneficial effects of the present invention are:
[0031] 1. The slurry of the present invention has low raw material cost, high window emissivity and high reflectivity; the present invention also provides a method for preparing a low-cost high-entropy soil material, which can significantly increase the hiding power of the coating. The slurry of the present invention is green and environmentally friendly, and can be applied on the surface of fabrics, building exterior walls, roofs, and oil tanks to effectively reduce the surface temperature of objects.
[0032] 2. The "atmospheric window" emissivity of the slurry for the radiation cooling coating of the present invention is as high as 94%, while the average reflection effect of ultraviolet-visible-infrared light is 92%. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 is the XRD diffraction spectrum of the powder material in Experimental Example 1;
[0034] Figure 2 The slurry reflectivity test results in Experimental Example 1;
[0035] Figure 3 This is the bandgap width test result diagram in Experimental Example 1;
[0036] Figure 4 This is the SEM photo of the A4 slurry in Example 1. DETAILED DESCRIPTION
[0037] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.
[0038] Example 1
[0039] Take 20 parts of aluminum oxide, 26 parts of niobium oxide, 16 parts of cerium rare earth, and 30 parts of lead oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the block precursor sample into the powder crusher again to obtain a uniformly mixed precursor powder (coarse powder).
[0040] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate). In this embodiment, the solvent is water. 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size is obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.
[0041] Use water as solvent, prepare 40% coarse powder solution, add 13% BYK111 dispersant, grind the slurry in a sand mill, monitor the particle size until it is 1-10μm, and the actual D50 particle size after grinding is 3.2μm. Pour the slurry into the feed bottle of the spray dryer, set the spray temperature to 150 degrees, and adjust the flow rate of the atomizing nozzle according to experience until a powder vortex is formed. Inject the obtained fine powder into a suspension sintering furnace, set the sintering degree to 1250 degrees, and obtain spherical powder after sufficient sintering.
[0042] The obtained spherical powder was reconfigured into a 30% solution, the solvent was water, 5% BYK111 dispersant was added again, and the solution was fully stirred with a disc stirrer. It should be noted that the spherical powder should be poured into the solution in batches under stirring conditions. After the solution becomes a uniform foam-free emulsion, it is poured out and stored, and the solution is named A4. In the A4 solution, the powder morphology can be observed by SEM electron microscope.
[0043] The four slurries were mixed in a mass ratio of A1:A2:A3:A4=1:1:0.5:0.15 to prepare a finished slurry.
[0044] The preparation method of the cerium group rare earth is as follows: the precursor powder is loaded into a corundum crucible, and heated in a melting furnace with stirring, wherein the heating program is as follows: the first section, the temperature range is 50-400 degrees, the time is 35 minutes; the second section, the temperature range is 00 degrees for insulation, the time is 30 minutes; the third section is 400-900 degrees, the time is 1 hour; the fourth section is 900-1400 degrees, the time is 2 hours; the fifth section is 1400 degrees constant temperature, the time is 4 hours; then the program is terminated. After the fifth section is kept warm for 3 hours, the corundum stirring paddle is lowered into the liquid, and slowly stirred at a speed of 60 revolutions per minute for 30 minutes, and then the stirring paddle is lifted. After the heating program is completed, the liquid is directly poured into water for cold quenching, and the powder in the water is filtered to obtain the coarse powder.
[0045] Test method: The coarse powder is subjected to XRD test, and the results are as follows Figure 1 As shown in the figure, the material structure is indeed amorphous. For the reflection performance test, the slurry needs to be prepared into a coating sample for testing. The specific method is to take 30g of water-based acrylic resin with a solid content of 35%, 60g of finished slurry, add appropriate amount of water to adjust the viscosity of the coating, and evenly apply the coating on the surface of the aluminum sheet. After the resin is completely cured and dried, use a UV-visible-infrared spectrophotometer to test the reflection effect. The results are as follows: Figure 2 As shown, the reflection effect can reach 93%. According to formula 1, the energy band result is calculated as follows: Figure 3 As shown in the figure, the bandgap reaches 3.7eV, which is higher than the 2.7-2.8eV of titanium dioxide. The emissivity data of the slurry was tested by an IR-1 hemispherical emissivity tester. At 25 degrees, the window emissivity at 8-14μm was measured to be 0.94, showing excellent emission performance.
[0046] Example 2
[0047] Take 35 parts of aluminum oxide, 35 parts of niobium oxide, 20 parts of cerium rare earth, and 16 parts of lead oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the block precursor sample into the powder crusher again to obtain a uniformly mixed precursor powder (coarse powder).
[0048] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate). In this embodiment, the solvent is water. 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size is obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.
[0049] Use water as solvent, prepare 40% coarse powder solution, add 13% BYK111 dispersant, grind the slurry in a sand mill, monitor the particle size until it is 1-10μm, and the actual D50 particle size after grinding is 3.2μm. Pour the slurry into the feed bottle of the spray dryer, set the spray temperature to 150 degrees, and adjust the flow rate of the atomizing nozzle according to experience until a powder vortex is formed. Inject the obtained fine powder into a suspension sintering furnace, set the sintering degree to 1250 degrees, and obtain spherical powder after sufficient sintering.
[0050] The obtained spherical powder was reconfigured into a 30% solution, the solvent was water, 5% BYK111 dispersant was added again, and the solution was fully stirred with a disc stirrer. It should be noted that the spherical powder should be poured into the solution in batches under stirring conditions, and after the solution becomes a uniform foam-free emulsion, it is poured out and stored, and the solution is named A4. The four slurries were mixed in a mass ratio of A1:A2:A3:A4=1:1.3:0.6:0.2 to prepare the finished slurry.
[0051] The preparation method of the cerium group rare earth is as follows: the precursor powder is loaded into a corundum crucible, and heated in a melting furnace with stirring, wherein the heating program is as follows: the first section, the temperature range is 50-400 degrees, the time is 35 minutes; the second section, the temperature range is 00 degrees for insulation, the time is 30 minutes; the third section is 400-900 degrees, the time is 1 hour; the fourth section is 900-1400 degrees, the time is 2 hours; the fifth section is 1400 degrees constant temperature, the time is 4 hours; then the program is terminated. After the fifth section is kept warm for 3 hours, the corundum stirring paddle is lowered into the liquid, and slowly stirred at a speed of 60 revolutions per minute for 30 minutes, and then the stirring paddle is lifted. After the heating program is completed, the liquid is directly poured into water for cold quenching, and the powder in the water is filtered to obtain the coarse powder.
[0052] Experimental Example 1
[0053] The coarse powder was subjected to XRD test, and the results are shown in the attached manual. Figure 1 As shown, the results show that the material structure is indeed amorphous. For the reflection performance test, the slurry needs to be prepared into a coating sample for testing. The specific method is to take 30g of water-based acrylic resin with a solid content of 35%, 60g of finished slurry, add appropriate amount of water to adjust the viscosity of the coating, and evenly apply the coating on the surface of the polyurethane fabric. After the resin is completely cured and dried, use a UV-visible-infrared spectrophotometer to test the reflection effect. The results are shown in the attached manual. Figure 2 As shown, the reflection effect can reach 93%. The energy band result is calculated according to formula 1:
[0054] Formula 1: (αhν)m=A(hν-Eg);
[0055] Where α is the absorptivity of the powder to the incident light. ν is the frequency of the incident photon, h is the Planck constant, A is the proportional constant, Eg is the band gap, and m is a constant value. For direct band gap semiconductor materials, m is equal to 2, and for indirect band gap semiconductor materials, m = 0.5.
[0056] As the instruction manual Figure 3 As shown, the bandgap reaches 3.7eV, which is higher than the 2.7-2.8eV of titanium dioxide. The emissivity data of the slurry was tested by an IR-1 hemispherical emissivity tester. At 25 degrees, the window emissivity at 8-14μm was measured to be 94%, showing excellent emission performance.
[0057] Comparative Example 1
[0058] A radiation cooling slurry is prepared in the same manner as in Example 1, except that no cerium rare earth is added to the raw materials. The specific method is:
[0059] Take 28 parts of aluminum oxide, 36 parts of niobium oxide, and 35 parts of lead oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the block precursor sample into the powder crusher again to obtain a uniformly mixed precursor powder.
[0060] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate). In this embodiment, the solvent is water. 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size is obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.
[0061] Use water as solvent, prepare 40% coarse powder solution, add 13% BYK111 dispersant, grind the slurry in a sand mill, monitor the particle size until it is 1-10μm, and the actual D50 particle size after grinding is 3.2μm. Pour the slurry into the feed bottle of the spray dryer, set the spray temperature to 150 degrees, and adjust the flow rate of the atomizing nozzle according to experience until a powder vortex is formed. Inject the obtained fine powder into a suspension sintering furnace, set the sintering degree to 1250 degrees, and obtain spherical powder after sufficient sintering.
[0062] The obtained spherical powder was reconfigured into a 30% solution, the solvent was water, 5% BYK111 dispersant was added again, and the solution was fully stirred with a disc stirrer. It should be noted that the spherical powder should be poured into the solution in batches under stirring conditions, and after the solution becomes a uniform foam-free emulsion, it is poured out and stored, and the solution is named A4. The four slurries were mixed in a mass ratio of A1:A2:A3:A4=1:1.3:0.6:0.2 to prepare the finished slurry.
[0063] Comparative Example 2
[0064] A radiation cooling slurry was prepared in the same manner as in Example 1, except that only slurry A1 with D50 = 21 μm was used for preparation. The specific method is as follows:
[0065] Take 25 parts of aluminum oxide, 30 parts of niobium oxide, 20 parts of cerium rare earth, and 25 parts of lead oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the blocky precursor sample into a powder crusher again to obtain a uniformly mixed precursor powder (coarse powder).
[0066] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate). In this embodiment, the solvent is water. 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size is obtained. By strictly controlling the particle size, a slurry A1 with a D50 of 21 μm is prepared. The slurry A1 and water are mixed in a ratio of 6.5:3.5 to prepare a finished slurry.
[0067] Comparative Example 3
[0068] A radiation cooling slurry was prepared in the same manner as in Example 1, except that only slurry A3 with D50 = 0.45 μm was used for preparation. The specific method is as follows:
[0069] Take 30 parts of aluminum oxide, 26 parts of niobium oxide, 17 parts of cerium rare earth, and 18 parts of lead oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Fully dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the block precursor sample into the powder crusher again to obtain a uniformly mixed precursor powder (coarse powder).
[0070] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate). In this embodiment, the solvent is water. 10 kg of coarse material powder solution is put into a sand mill for sand grinding. The grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size is obtained. By strictly controlling the particle size, a slurry A3 with a D50 of 0.45 μm is prepared. The mixed slurry A3 and water are mixed in a ratio of 6.5:3.5 to prepare a finished slurry.
[0071] Comparative Example 4
[0072] A radiation cooling slurry is prepared in the same manner as in Example 1, except that the cerium rare earth in the raw material is replaced with various high-purity oxides to obtain high entropy products. The specific method is:
[0073] Take 20 parts of aluminum oxide, 25 parts of niobium oxide, 18 parts of high entropy product, and 30 parts of lead oxide. After fully mixing these raw materials, add a certain amount of water and wet grind them in a planetary ball mill. The ball mill speed is 400 rpm and the grinding time is 12 hours. The ratio of large, medium and small balls is 3:4:3, and the volume ratio of air: liquid: ball in the cavity is controlled at 1:1:1. After grinding, filter the grinding beads with a 40-mesh screen to obtain a coarsely ground slurry. Dry the coarsely ground slurry in a 90-degree oven to obtain a precursor sample that is agglomerated. Put the blocky precursor sample into a powder crusher again to obtain a uniformly mixed precursor powder (coarse powder).
[0074] The preparation method of the high entropy product is:
[0075] A 40% coarse material powder solution is prepared, wherein the dispersant content is 12%, and the dispersant is BYK111 type dispersant. The solvent depends on the final coating product requirements (for water-based coating slurry, the solvent is water; for oil-based coating, the solvent is butyl acetate). In this embodiment, the solvent is water. 10 kg of coarse material powder solution is put into a sand mill for sand grinding, and the grinding ball particle size is 0.5 mm. The slurry particle size is detected once every 15 minutes with a laser particle size analyzer until the slurry with the target particle size is obtained. By strictly controlling the particle size, slurry A1 with a D50 of 21 μm, slurry A2 with a D50 of 6.2 μm, and slurry A3 with a D50 of 0.45 μm were prepared respectively.
[0076] Use water as solvent, prepare 40% coarse powder solution, add 13% BYK111 dispersant, grind the slurry in a sand mill, monitor the particle size until it is 1-10μm, and the actual D50 particle size after grinding is 3.2μm. Pour the slurry into the feed bottle of the spray dryer, set the spray temperature to 150 degrees, and adjust the flow rate of the atomizing nozzle according to experience until a powder vortex is formed. Inject the obtained fine powder into a suspension sintering furnace, set the sintering degree to 1250 degrees, and obtain spherical powder after sufficient sintering.
[0077] The obtained spherical powder was reconfigured into a 30% solution, the solvent was water, 5% BYK111 dispersant was added again, and the solution was fully stirred with a disc stirrer. It should be noted that the spherical powder should be poured into the solution in batches under stirring conditions, and after the solution becomes a uniform foam-free emulsion, it is poured out and stored, and the solution is named A4. The four slurries were mixed in a mass ratio of A1:A2:A3:A4=1:1:0.5:0.15 to prepare a finished slurry.
[0078] Experimental Example 2
[0079] The slurries of Comparative Examples 1-4 and Example 1 were tested for reflection performance, emissivity and hiding power. The methods for reflection performance and emissivity testing were the same as those for Example 1. The results were calculated based on the average values. The results are shown in Table 1.
[0080] Table 1
[0081]
[0082]
[0083] Among them, the hiding power test method is the whiteness test, which is to apply the paint on the surface of black test paper and white test paper respectively. After fully drying, use a whiteness tester to test the whiteness of the coating on the surface of black test paper and white test paper respectively. The ratio of the whiteness of the coating on the surface of black test paper to the whiteness of the coating on the surface of white test paper is the hiding power. Obviously, the higher the ratio, the less influence the color of the base layer under the paint has on the whiteness of the paint, that is, the higher the hiding power.
[0084] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. Rare earth slurry for white dye with radiation cooling function, characterized in that: The raw materials include 20-35 parts of aluminum oxide, 25-36 parts of niobium oxide, 13-20 parts of cerium rare earth, and 16-35 parts of lead oxide by weight; The cerium family rare earth is obtained by separating the raw rare earth by a sodium sulfate double salt precipitation method or a sodium carbonate double salt precipitation method; The method for preparing the rare earth slurry comprises the following steps: S1: mixing the aluminum oxide, niobium oxide, cerium group rare earth and lead oxide and crushing them; S2: sintering the crushed powder at high temperature, and then quenching the sintered molten liquid in cold water to obtain a coarse product powder; S3: adding the crude product powder into a solvent for grinding to obtain A1 slurry with a particle size of 15-25 μm, A2 slurry with a particle size of 5-10 μm, and A3 slurry with a particle size of 0.3-0.7 μm respectively; S4: Grind the crude product powder with water, then perform atomization drying, and perform a second sintering at high temperature. The obtained powder is dispersed in a solvent to obtain A4 slurry; S5: Mix the A1 slurry, A2 slurry, A3 slurry and A4 slurry to obtain.
2. The rare earth slurry according to claim 1, characterized in that: In step S2, the particle size of the crushed powder is 30-40 mesh.
3. The rare earth slurry according to claim 1, characterized in that: In step S2, the first sintering temperature is 1360-1400°C; And / or, the first sintering time is 4-4.5h.
4. The rare earth slurry according to claim 1, characterized in that: In step S3, the particle size is a median particle size.
5. The rare earth slurry according to claim 1, characterized in that: In step S4, the particle size of the coarse product powder after grinding is 1-5 μm.
6. The rare earth slurry according to claim 1, characterized in that: In step S4, the temperature of the second sintering is 1230-1250°C; And / or, the second sintering time is 30-50 min.
7. The rare earth slurry according to claim 1, characterized in that: The weight ratio of the A1 slurry, A2 slurry, A3 slurry and A4 slurry is 1:0.8-1.3:0.4-0.6:0.1-0.
2.
8. The rare earth slurry according to claim 1, characterized in that: In steps S4 and S5, the solvent includes water or butyl acetate; And / or, the solid content of the A1 slurry, A2 slurry, A3 slurry and A4 slurry is 30-40%.
Citation Information
Patent Citations
Selective radiation refrigeration coating and composite material and application method thereof
CN110317521A
Radiative Cooling Coatings and Their Applications
CN110684463B
Daytime radiation refrigeration coating
CN115386273A
Radiation-cooling coating material
CN109852171A
Cement-based radiation refrigeration dry powder paint, building coating and coating preparing method
CN110105798A